The Effect Of Rare-Earth Substitution On The Properties Of Bismuth Titanate Prepared By Low Temperature Combustion Technique - Haji Azlan, Umar Al-Amani (2013)
In this research work, the production of bismuth titanate (Bi4Ti3O12 or BIT) at low temperature using combustion method was investigated to minimize the volatilization of Bi that deteriorates the dielectric and ferroelectric properties. In order to embark upon this problem, in the first phase, two combustion methods; sol-gel auto-combustion (SGAC) and precipitation assisted low-temperature combustion (PLTC) were investigated in terms of phase formation, structural, powder and grain morphology, dielectric and ferroelectric properties. The use of SGAC had resulted in single phase BIT with high degree of crystallinity at 750oC, particle size of 120 nm, spherical in shape with the highest relative density of about 84% at 1100oC. The dielectric constant (εr), dielectric loss (tan δ), remanent polarization (Pr) and coercive field (Ec) of BIT by SGAC were 119, 0.008, 6.3 μC/cm2 and 20 kV/cm, respectively. For PLTC, the single phase BIT with high crystallinity was formed at around 290oC without calcination, with particle size of 50 nm which is platey in shape. The highest relative density of 86% was achieved at 1000oC. The values of εr, tan δ, Pr and Ec of BIT by PLTC were 113, 0.007, 6.8 μC/cm2 and 26 kV/cm, respectively. For the second phase, rare-earth substituted-BIT was investigated and it was found that La and Nd exhibited similar characteristic, whereby both resulted in single phase regardless of La and Nd content. The presence of pyrochlore phase was detected in BSmT samples when the content Sm above 0.5. La substituted-BIT (BLaT100) exhibited high εr (212) and low tan δ (0.005). This is as a result of uniform grain size (1.6 μm in length and 0.3 μm in width) with the improved relative density (91%) of the sample. However, for ferroelectric properties, the maximum Pr (9.6 μC/cm2) with low Ec (18 kV/cm) were observed at BLaT75 and BLaT100 samples, respectively. The best optimum sample for Nd substituted-BIT was BNdT100 with εr and tan δ values of 231 and 0.005, respectively. The average grain size was 1.3 μm in length and 0.3 μm in width with improved relative density of 90% were achieved in BNdT100 sample. For ferroelectric properties, the maximum Pr (9.2 μC/cm2) with low Ec (34 kV/cm) were identified from BNdT75 and BNdT100 samples, respectively. In BSmT system, the improved dielectric properties were obtained from BSmT100 sample with εr and tan δ were 139 and 0.004, respectively. The improved dielectric results were attributed to the uniform grain size (1.9 μm in length and 0.4 μm in width). Nevertheless, the low ferroelectric performance in BSmT100 is due to low Pr (4.4 μC/cm2) and high Ec (64.3 kV/cm).